HUBUNGAN MOTIVASI BERWIRAUSAHA DENGAN HASILBELAJAR SISWA DALAM MATA PELAJARAN PAKET KEAHLIAN KRIYA TEKSTIL SMKN 4 PADANG - AHAD RAMDANI, Drs. Yusron Wikarya, M.Pd. Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2017)
The purpose of this study was to determine: 1) The relation of entrepreneurship motivation with student's learning outcomes in the subject of batik in the department of textile and craft in SMKN 4 Padang, 2) The relation of entrepreneurship motivation with students' learning outcomes in the subject of screen printing in the department of textile and craft in SMKN 4 Padang. Type of this research is quantitative study using correlation method. Data analysis technique used is the product moment correlation technique. The population in this study were all students department of textile and craft in SMKN 4 Padang. The samples were XI grade students of the department of textile and craft in SMKN 4 Padang which was selected by using purposive sampling technique. The type of data collected in this research is primary data and secondary data. Based on the analysis of the data, the relation of entrepreneurship motivation to learn batik obtained the coefficient correlation of 0.409. The result of the relation of entrepreneurship motivation to learn screen printing results in the coefficient correlation of 0.344. Based on the results, there is a strong relation between the variables of enterpreneurship motivation and the variables of learning batik and screen printing motivations.Keyword: motivation, the subject of batik, the subject of screen printing, and learning outcomes.